The association between YouTube use and knowledge of human papillomavirus-related cancers - Vanessa G. Dorismond; W. John Boscardin; George F. Sawaya (Elsevier, 2023)
Objective: To examine the association between YouTube usage and HPV-related cancer knowledge (cervical, anal, oral and penile). Study design: Cross-sectional study using data from the Health Information National Trends survey conducted between 2017 and 2020 (N = 16,092). Logistic regression was used to analyze the independent effect of YouTube use on cancer knowledge, controlling for sociodemographic characteristics. Results: Respondents' knowledge of HPV-related cancers varied: 49.9% about cervical, 18% anal, 20.1% oral and 20.4% penile cancers. YouTube use was associated with increased knowledge for all cancers (cervical: OR 2.66, 95% CI 2.04, 3.46; anal: OR 1.83, 95% CI 1.32, 2.53; oral: OR 1.89, 95% CI 1.37, 2.61; penile OR 2.00, 95% CI 1.44, 2.77) in models adjusted for all covariates. Other independent predictors of HPV-related cancer knowledge included female gender, younger age, a higher income, and higher education. Conclusion(s): YouTube could play an important role in educating people about HPV-related cancers and should also target other populations, such as males and those with less formal education. Innovation: The study provides novel insights into the potential of YouTube as an educational tool for promoting cancer knowledge with the goal of cancer prevention.